Re-shaping the Model of Economic Growth of the CEE Countries - Makrevska disoska, Elena (Tallinn Law School, School of Business and Governance, Tallinn University of Technology, 2016)
The goal of this paper is to stress the importance of changing the present growth strategy of Central and Eastern European (CEE) economies. The economic model of resource and debt intensive growth they have enjoyed in the past two decades have proved to be ineffective and unsustainable. Given that the CEE growth model cannot be identified separately from the EU as a whole, we try to propose possible policy measures that would stimulate growth in the CEE in context of the policies at the EU level.
Keywords: Central and Eastern Europe; sustainability; economic growth